Reliability and validity of three portable devices for quantifying spatiotemporal parameters in runners of different athletic abilities during treadmill running - Rodríguez-Barbero, S.; González-Mohíno, F.; González Ravé, J. M.; Rodrigo-Carranza, V.; Santos-García, D. J. (Sports Biomechanics, 2025)
This study aimed to evaluate the validity and reliability of a wearable device and a phone application for measuring spatiotemporal parameters and their relationship with running economy (RE) by comparing them with photocell data in runners of different abilities. Twenty-three male runners were divided into well-trained and recreational groups and performed a 4-min running bout at 17 and 13 km·h-1 respectively. During the bout, were measured the spatiotemporal parameters with three devices (Stryd, Runmatic, and Optojump) and RE with a gas analyser. Pearson correlation showed perfect relationships for stride frequency (SF) and stride length (SL) between the devices, and moderate for flight time (FT) and contact time (CT). There were no correlations between the spatiotemporal parameters and RE measurements. Coefficient of variation was ~ 5% in all devices for CT, SF, and SL, and higher for FT (15-24%). CT was underestimated (15-16% with Runmatic and Stryd, respectively) and FT was overestimated (36-40%) compared to Optojump. Bland-Altman plots revealed that Runmatic could be a more accurate system than Stryd. In conclusion, both devices were valid tools for measuring spatiotemporal parameters during running at RE speed. Runmatic was more valid and reliable in comparison with Stryd. In addition, at lower running speeds the devices showed less reliability.